2017
DOI: 10.3389/fpls.2017.01967
|View full text |Cite
|
Sign up to set email alerts
|

Metalaxyl Effects on Antioxidant Defenses in Leaves and Roots of Solanum nigrum L.

Abstract: Overuse of pesticides has resulted in environmental problems, threating public health through accumulation in food chains. Phytoremediation is a powerful technique to clean up contaminated environments. However, it is necessary to unravel the metabolic mechanisms underlying phytoremediation in order to increase the efficiency of this process. Therefore, growth, physiological and biochemical responses in leaves and roots of Solanum nigrum L. exposed to the commonly used fungicide metalaxyl were investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
0
38
1
Order By: Relevance
“…Metalaxyl and, to a lesser extent, phosphorous acid treatments, protected the plants from death, but the surviving plants showed very poor growth performance compared to the surviving plants of the control treatment. Regarding metalaxyl, Sousa et al (2017) reported a decrease in RuBisCO activity in Solanun nigrum, which resulted in photosynthesis inhibition and an abrupt decrease in plant growth. However, we think this was not the case in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Metalaxyl and, to a lesser extent, phosphorous acid treatments, protected the plants from death, but the surviving plants showed very poor growth performance compared to the surviving plants of the control treatment. Regarding metalaxyl, Sousa et al (2017) reported a decrease in RuBisCO activity in Solanun nigrum, which resulted in photosynthesis inhibition and an abrupt decrease in plant growth. However, we think this was not the case in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Plants need glutathione or g-glutamylcysteine containing homologues to survive [ 25 ]. The roles of glutathione include xenobiotic detoxification, antioxidant biochemistry and redox homeostasis, under normal or stress situations, and it constitutes one of the principal cellular antioxidant systems with other antioxidant defenses (polyphenols, flavonoids, tocopherols and ascorbate) to scavenge reactive oxygen and nitrogen species [ 26 ]. In plant physiological conditions without stress, tissues such as leaves maintain measurable GSH:GSSG ratios of at least 20:1 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results were expressed as mean ± SD (standard deviation) and analyzed by three-way ANOVA (SPSS Statistica 23, SPSS Inc., Chicago, IL, USA), with genotype (G), treatment (T) and organs (O) as fixed variables (ANOVA results in supplementary table 2 ) as previously described in our previous publications 13 , 43 . In cases of significant interactions between factors, one-way ANOVA was performed for each factor, and Tukey’s multiple range tests were used to determine significant differences among means.…”
Section: Methodsmentioning
confidence: 99%